Analisis Framing Negatif dan Pengaruhnya Terhadap Stereotip Budaya Dalam Media Sosial: Studi Kasus Kontroversi "Rendang Hilang" oleh Conten Creator @Willie Salim di TikTok - Nur Fadia Rusly; Nikmah Suryandari (Jurnal Multidisiplin Indonesia, 2025)
This study analyzes negative framing and its impact on cultural stereotypes in the "Rendang Hilang" controversy by content creator @Willie Salim on TikTok. Through a qualitative approach with framing analysis and comment content analysis, this study identifies how negative framing in videos and echo chamber effects reinforce stereotypes against Palembang society. The results showed that the visualization and narrative chosen in the video, combined with social media algorithms, exacerbated social prejudice and polarization of opinions. The implications of this study highlight the importance of media literacy and critical awareness in responding to viral content on social media.